Yuki Chan in Brontë country - Jackson, Mick (Faber & Faber, 2016)
Yukiko tragically lost her mother ten years ago. After visiting her sister in London, she goes on the run, and heads for Haworth, West Yorkshire, the last place her mother visited before her death. Against a cold, winter, Yorkshire landscape, Yuki has to tackle the mystery of her mother's death, her burgeoning friendship with a local girl, the allure of the Brontes and her own sister's wrath
Keywords: Yorkshire (England) / Fiction